2023
DOI: 10.24256/ideas.v10i2.3224
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perspective on the Use of Google Sites in General English Class at Higher Education

Abstract: Technology plays a significant role in English Language Teaching during the pandemic. There are several platforms that both teachers and students need to adapt to. Google seems to have a major role in developing platforms for both teachers and students. However, among those platforms, this study focuses on the use of E-Module arranged using the Google Sites platform as supplementary material in General English classes. Google Sites was chosen as it is a web-based module that teachers can personalize to fulfill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Regarding students' overall perceptions, the findings supported that university students had highly positive perceptions of towards the application of the Google tools for their online English courses learning. These were consistent with the results from [42][43][44][45][46][47][48][49][50][51][52] in which students felt like using the Google tools, and emphatically perceived the tools as helpful, efficient, and interesting learning aids. Also, students made it abundantly clear that the utilization of Google products in the process of teaching and learning English is unquestionably doable, as was clearly demonstrated by the students.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Regarding students' overall perceptions, the findings supported that university students had highly positive perceptions of towards the application of the Google tools for their online English courses learning. These were consistent with the results from [42][43][44][45][46][47][48][49][50][51][52] in which students felt like using the Google tools, and emphatically perceived the tools as helpful, efficient, and interesting learning aids. Also, students made it abundantly clear that the utilization of Google products in the process of teaching and learning English is unquestionably doable, as was clearly demonstrated by the students.…”
Section: Discussionsupporting
confidence: 87%
“…Findings in [45] on students' perception of Google Meet revealed that students were content, safe, self-assured, brave, and confident psychologically, and that there were no barriers during the Google Meet video conferencing during the English-speaking class. Studies [46], [47] on students' perceptions of Google Sites shared similar results. Students perceived Google Sites as a quite helpful, interesting, interactive, and easy tool to use [46], and learning with Google Sites was efficient, fun, and motivating [47].…”
Section: Previous Studies On Students' Perceptions Of Google Tools In...mentioning
confidence: 55%
See 2 more Smart Citations